A Comparative Advantage of Livestock Production in Brunei Darussalam - Abdul Rahman, Anjah @ Amzah (2000)
Brunei policy measures are geared toward conserving foreign exchange. Presently, government bans the importation of eggs and regulates the importation of fresh, chilled and frozen beef and chicken meat while the importation of live animals is subjected to stringent health measures. While the local production is given a tremendous supports likes the provision of basic infrastructure facilities, input subsidies and output price control. These give repercussions to the whole economy and play a role in directing the course of the industry. Primary data through census were collected in 1998 where a total of 94 broiler farms, 21 layer farms, 1 feedlot beef operator and 4 commercial goat farms were involved. Indicators of NPR, EPR, DRC, RCR and NEB were used to estimate the impact of government intervention and comparative advantage. Prior to these, the cost and the profit performance are analysed in financial and economic terms.The results appear that the policy of the government give a minimal impact to the domestic production. A wedge between domestic and border price give slight protection to domestic producers' ranges from a minimum NPR of 6.83 percent in broiler to 95.12 percent in goat. EPR in egg based on farm size ranges from 175 percent in very large to 748 percent in medium. Even though the layer farms are protected, their continued existence, remain doubtful. This is true, that the small and medium failed to sustain their growth as shown by negative social profitability, and is an indication of inefficient producing units and so with other livestock commodities except in very large layer and broiler and goat farm. The lowest EPR is broiler having an average of 120 percent, while in the goat is 239.03 percent. The analysis of private profitability shows that all enterprises are generating profit. Financially, the highest profit recorded is the goat production by $8.7533 per kilogram dressed weight. In egg, the very large farm generates the highest positive private profit among its category by $33.5344 per 100 dozen. There is also a profit in all broilers farms. The results of DRC, RCR and NEB show comparative disadvantage except for very large layer and broiler farm and goat. A lower the cost of production vis-a-vis efficiently operated attributes the source of comparative advantage. The non-ruminant is proven to be more effective in saving the foreign exchange and followed by goat. Therefore, recommendation should be concentrated on the promotion of the non-ruminant and goat sectors, continues provision of the critical infrastructure support in the form of comprehensive R&D, credit and marketing is a priority.